2011
DOI: 10.1111/j.1540-8167.2011.02164.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Catheter Ablation for Atrial Fibrillation Prior to Atrial Septal Defect Closure

Abstract: Percutaneous Radiofrequency Catheter Ablation. Patients with an atrial septal defect (ASD) commonly have atrial fibrillation (AF) and closure of the ASD rarely controls the arrhythmia. We report on the management of 4 patients with recurrent medically refractory AF in the setting of an unrepaired ASD who underwent percutaneous RFA prior to ASD closure. In 3 of the 4 patients AF was controlled after ablation without antiarrhythmic drug therapy and in the fourth patient AF was controlled with antiarrhythmic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…There are also very limited reports of RF catheter ablation prior to device closure of ASD at a separate procedure. 45…”
Section: Pre-emptive Treatmentmentioning
confidence: 99%
“…There are also very limited reports of RF catheter ablation prior to device closure of ASD at a separate procedure. 45…”
Section: Pre-emptive Treatmentmentioning
confidence: 99%
“…Endovascular pulmonary vein isolation (PVI) has been described in a limited number of patients. Four patients with an ASD and either paroxysmal ( N = 2) or persistent ( N = 2) AF were scheduled for percutaneous closure of the ASD [ 31 ]. Prior to closure, endovascular PVI was performed in all 4 patients; additional lesions were created in the 2 patients with persistent AF including a circular lesion around the superior caval vein and a linear lesion connecting the right and left pulmonary veins and mitral isthmus line.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…In our population no other than concomitant surgical procedures were performed although several other types of invasive therapy have been described in literature and proven to be safe and effective. [27][28][29] Our own group showed that a pulmonary vein isolation together with ASD closure in the same procedure can be performed safely with a good effect on recurrence rate in symptomatic patients with AF and an ASD. 30 Future studies are needed on the best treatment option of AF in patients with an ASD.…”
Section: Discussionmentioning
confidence: 99%